A precision estimating database - Takkin Yugala; Ogunlana, Stephen O.; Pichai Nimityongskul; Prapon Phasukyud; Jearkjirm, Vithool; Royal Thai Government (Bangkok : Asian Institute of Technology, 1994)
Precision Estimating Plus software is a tool developed for performing construction cost estimating. It consists of the main program that manipulates a database containing construction information. In application, the measured dimension of the work piece is applied to this information to transform the raw material to a finished material that serve its function. The processed information produced is the estimate and is presented in the form of quantities and prices. Therefore, the information contained in the database is the heart of the software. In this research, the development of such database is made using the local construction information. The introduction of Precision Estimating Plus to the construction management class will enable the students to gain a better knowledge of the computational methods used in computerized estimating. From its use, new ideas of improving and developing this type of software to suit the local construction industry may be obtained.
A thesis submitted in partial fulfillment of the requirements for the degree of master of engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Construction industry -- Data processing; Construction industry -- Costs